JALAL AL-DIN AL-RUMI DAN TAREKAT MAULAWIYYAH: Melacak Sejarah Pertumbuhan, Perkembangan, dan Ajaran Tarekat Maulawiyyah - Angga Arifka (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2022)
This article discusses one of the Sufi orders in Islam, namely Maulawiyyah. Jalal al-Din al-Rumi, to which this Sufi order refers, is the great figure who is immensely close to the realm of poetry and of music. It is unsurprising that the Maulawiyyah order has its feature close to art. This article, as library research, employs an analytic-descriptive method to unraveling both primary and secondary data which are accessible. The findings obtained in this article are that the Maulawiyyah order at the first time became institutionalized owing to Sultan Walad, the Rumi’s son. Similarly, the ceremony and the ritual in the order commenced to be developed since the era of the Sultan Walad’s leadership. Besides, the Maulawiyyah order is one of the Sufi orders that has its own uniqueness in its spiritual method and ceremony. Music and whirling dervishes become a peculiar way that must be practiced by each dervish in the order. According to the Maulawiyyah order, music can be a path to being able to be close to the God. In other words, music itself has spiritual value in it. Such typicality becomes the Maulawiyyah order’s feature.